The Sydney playground project- levelling the playing field: a cluster trial of a primary school-based intervention aiming to promote manageable risk-taking in children with disability. (December 2015) - Bundy, Anita; Wyver, Shirley; Beetham, Kassia; Ragen, Jo; Naughton, Geraldine; Tranter, Paul; Norman, Richard; Villeneuve, Michelle; Spencer, Grace; Honey, Anne; Simpson, Judith; Baur, Louise; et al.
Abstract Background Providing children and adults with opportunities to engage in manageable risk taking may be a stepping stone toward closing the gap in life conditions currently experienced by young people with disabilities. We aim to demonstrate the effectiveness of a simple, innovative program for 1) changing the way parents and teachers view manageable risk-taking for children with disabilities and 2) increasing the level of responsibility that children take for their own actions, as seen on the school playground. Methods/Design We will employ a cluster repeated measures trial with six Sydney-area primary-school-based programs for children with disabilities. The intervention comprises two arms. 1) Risk-reframing- teachers and parents will participate together in small group intervention sessions focusing on the benefits of manageable risk-taking; 2) Introduction of play materials- materials without a defined purpose and facilitative of social cooperation will be introduced to the school playground for children to use at all break times. A control period will be undertaken first for two school terms, followed by two terms of the intervention period. Outcome measures will include playground observations, The Coping Inventory, qualitative field notes, and The Tolerance of Risk in Play Scale. Discussion New national programs, such as Australia's National Disability Insurance Scheme, will place increasing demands on young people with disabilities to assume responsibility for difficult decisions regarding procuring services. Innovative approaches, commencing early in life, are required to prepare young people and their carers for this level of responsibility. This research offers innovative intervention strategies for promoting autonomy in children with disabilities and their carers. Trial Registration Australian and New Zealand Clinical Trials Registration NumberACTRN12614000549628 (registered 22/5/2014).